PERBANDINGAN PERHITUNGAN PENETAPAN BIAYA JASA SIMPAN PADA PEGADAIAN SYARIAH DENGAN BIAYA SEWA MODAL PADA PEGADAIAN KONVENSIONAL - Afrila Mu'arrofah (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
Pegadaian is the only business entity in Indonesia that officially has a license to carry out financial institution activities in the form of financing in the form of distributing funds to the public on the basis of pawn law. The emergence of institutions that implement a pawn system in Indonesia, such as pawnshops, has become a new alternative for people who need large amounts of funds quickly and with a transaction process that is not difficult. Customers can use gold, electronic goods and other valuables to be pawned as collateral. Along with the many developments in sharia-based financial institution products in Indonesia, PT. Pegadaian also produce sharia-based products, better known as pegadaian syariah. Researchers want to examine the comparison of the calculation of costs borne by customers at conventional pegadaian and pegadaian syariah. The researcher used a qualitative approach method. The results of this research show that the costs that must be borne by customers when making loans at pegadaian, both conventional pegadaian and pegadaian syariah, show that pegadaian syariah are more convenient than pegadaian.